Molecular Genetic Mechanisms of Influenza A Virus Replication and Mechanisms of Action of Etiotropic Medications - M. N. Dunaeva (Антибиотики и Химиотерапия)
Influenza is an acute respiratory viral infection, known for its epidemics and pandemics, claiming millions of lives everywhere. Influenza A virus (Orthomyxoviridae family), whose genome consists of 8 RNA segments of negative polarity, is widespread due to its patterns of variability, which determine the development of resistance, for example, to antiviral drugs. Reassortment mechanisms and point mutations in the influenza A virus genome can lead to a great variety of different variants of this pathogen. The considered life cycle of the influenza A virus with a detailed description of the molecular genetic features of its structures allows us to highlight the advantages and disadvantages of the etiotropic therapy used, affecting different stages of virus replication from the point of view of evidence-based medicine in aspects related to its resistance.